Coordinates of Power and Performance: Festivals as Sites of (Re)Presentation and Reclamation in Sardinia - Magliocco, Sabina (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
This article examines festivals and related forms of public culture in Sardinia as performance events which construct and negotiate meanings for both hosts (the dominated culture, in the case of Sardinia) and guests (tourists), serving as sites for the creation of identity and authenticity. It documents the emergence of “festival reclamation,” a phenomenon in which subjugated groups reclaim or reappropriate (re)presentations of them created by the dominant culture. Festival reclamation may entail the reappropriation or recreation of a separate festival as an exquisitely local celebration after a larger festival has become a tourist attraction. Thus when a town’s primary festival no longer performs an identity narrative to which the population can subscribe, the community may choose to transform the festival through new activities, or to designate a new, separate festival to perform the identity with which the community identifies. This article examines these processes as part of the phenomenon of globalisation/localisation.